Pengaruh Regret Aversion Bias Dan Overconfidence Terhadap Pengambilan Keputusan Investasi Cryptocurrency Pada Generasi Z - Ardiansyah Japlani; Nani Septiana; Muammar Khadafi (Universitas Muhammadiyah Metro, 2025)
Behavioral Finance is a phenomenon of a person's psychology that can affect an investor in financial activities, this financial behavior can occur due to the irrational nature of an investor, especially in making investment decisions. This study has the aim of knowing whether regret aversion bias affected cryptocurrency investment decision making in generation z. To determine whether Overconfidence affected investment decision making in generation z. To find out whether Overconfidence affected cryptocurrency investment decision making in generation z. And to find out whether regret aversion bias and overconfidence affected cryptocurrency investment decision making in generation z and find out what the impact was. This study used a quantitative method with purpose sampling where the sample of this study amounted to 60 respondents who were generation z cryptocurrency investors. Data analysis used instrument requirement testing, namely validity and reliability tests. The analysis requirements test used normality test, linearity test and homogeneity test. And hypothesis testing used multiple linear regression analysis test, partial test (T test). simultaneous test (F test), and test the coefficient of determination (R2). By using the SPSS software application program. The results showed that 1). Regret aversion bias had a positive and significant effect on cryptocurrency investment decision making in generation z. 2). Overconfidence had a positive and significant effect on cryptocurrency investment decision making in generation z. and 3). Regret aversion bias and overconfidence had a significant effect on cryptocurrency investment decision making in generation z.